(untitled) (AYUSHDHARA, 2022)
A daily routine is essential to maintain health by bringing the fundamental changes required in body, mind, and spirit. An appropriate routine helps to establish the necessary structure for Human beings to maintain the equilibrium of Tridoshas. Biological rhythms like Circadian, Ultradian, and Infradian rhythms maintain the bodily functions regulating with an internal clock in a rhythmic way. Each Dosha exhibits diurnal variations. It also varies according to digestion phase and age. Age of the individual, Circadian rhythm and food intake are the basic factors that influence the physiology of the human body. Certain Environmental factors and bodily changes cause the Circadian rhythm to be out of sync, leading to many unhealthy conditions and are termed as Circadian rhythm disorder. A befitting routine has been described elaborately in the classical texts of Ayurveda in the form of Dinacharya, Ruucharya etc, which specifies out a daily, also as seasonal routine, for people to follow in order to enjoy optimal health and harmonious existence. The concepts mentioned in Ayurveda make us understand the best time for daily routines by keeping Doshic rhythms at an optimal level. Understanding the circadian rhythm in Ayurveda, causes for its derangement, its pathogenesis and ways to reset the circadian rhythm as mentioned in Ayurveda is needed to maintain health and to avoid present-day lifestyle disorders.